Dependence of reversed-phase liquid chromatographic retention for aripiprazole and some related chemical impurities on the main elution parameters. Issue 2 (20th January 2016) - Soponar, Florin; Sandru, Mihaela; David, Victor
ABSTRACT: The present study focuses on the chromatographic behavior of a novel atypical antipsychotic drug, aripiprazole, and its five chemical related impurities. The experiments were performed on a Zorbax SB-C18 column (150 mm × 4.6 mm, 5 µm particle size), whereas the detection was provided by an UV-Vis DAD detector set at 254 nm. The influences of the organic modifier, column temperature, and the pH of the mobile phase on the retention of the six compounds were studied. From these dependences some molecular descriptors and thermodynamic parameters that are important in drug characterization were evaluated. Also, the effect of two different acids added to the mobile phase (phosphoric acid and trifluoroacetic acid) on the retention behavior for chosen compounds was studied. GRAPHICAL ABSTRACT: